2010
DOI: 10.4103/0975-7406.62706
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a headspace gas chromatographic method for the determination of residual solvents in arterolane (RBx11160) maleate bulk drug

Abstract: Objective:Arterolane maleate is an antimalarial drug currently under Phase III clinical evaluation, and presents a simple, economical and scalable synthesis, and does not suffer from safety problems. Arterolane maleate is more active than artemisinin; and is cheap to produce. It has a longer lifetime in the plasma, so it stays active longer in the body. To provide quality control over the manufacture of any API, it is essential to develop highly selective analytical methods. In the current article we are repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…These changes to the genetic material, caused by exposure to very low levels of a genotoxin, can lead to cancer. While ICH published adequate controls for general process-related impurities (Q3A, Q3B), Pharmaceutical Genotoxic impurities (GTI) gained global prominence when regulatory bodies like European Medicines Agency (EMEA) and United States Food and Drug Administration (USFDA) [4,5] some few years back published stringent qualification thresholds lower than the default values set by ICH guidelines. These dictums confirmed that the existing ICH thresholds may not be acceptable for such DNA-reactive genotoxins or carcinogenic impurities.…”
Section: Molecular Formula = C35h38cl2n8o4mentioning
confidence: 99%
“…These changes to the genetic material, caused by exposure to very low levels of a genotoxin, can lead to cancer. While ICH published adequate controls for general process-related impurities (Q3A, Q3B), Pharmaceutical Genotoxic impurities (GTI) gained global prominence when regulatory bodies like European Medicines Agency (EMEA) and United States Food and Drug Administration (USFDA) [4,5] some few years back published stringent qualification thresholds lower than the default values set by ICH guidelines. These dictums confirmed that the existing ICH thresholds may not be acceptable for such DNA-reactive genotoxins or carcinogenic impurities.…”
Section: Molecular Formula = C35h38cl2n8o4mentioning
confidence: 99%
“…Literature survey reveals Automated Solid Phase Extraction and Liquid Chromatographic Method 3 , Capillary Zone Electrophoresis 4 , HPLC 5 and LC/MS/MS [6][7][8][9][10][11][12] methods for the estimation of Piperaquine phosphate alone or in combination with other drugs in pharmaceutical formulation and biological samples where as headspace gas chromatographic 13 methods for the estimation of Arterolane maleate alone in pharmaceutical formulation and biological samples. There are very few reported methods for the simultaneous determination of Arterolane maleate and Piperaquine phosphate by RP-HPLC in pharmaceutical dosage forms 14,15 .…”
Section: Fig 2: Structure Of Piperaquine Phosphatementioning
confidence: 99%
“…The static headspace GC is a conventional and powerful analytical technique that has been adopted and recommended by the European Pharmacopoeia and the United States Pharmacopoeia for the determination of residual solvents within quality control of pharmaceutical products . Relative simplicity of sample preparation, sensitivity and elimination of GC system contamination by unwanted non‐volatile substances belong to the main benefits of the headspace technique . However, analysis of some specific matrices for the RS content requires a special sample pretreatment.…”
Section: Introductionmentioning
confidence: 99%